Safety, efficacy, and reproducibility of cavotricuspid isthmus ablation guided by the ablation index: acute results of the FLAI study. Issue 2 (19th November 2020) - Viola, Graziana; Stabile, Giuseppe; Bandino, Stefano; Rossi, Luca; Marrazzo, Natale; Pecora, Domenico; Bottoni, Nicola; Solimene, Francesco; Schillaci, Vincenzo; Scaglione, Marco; Ocello, Salvatore; Baiocchi, Claudia; et al.
Abstract: Aims: Ablation index (AI) is a marker of lesion quality during catheter ablation that incorporates contact force, time, and power in a weighted formula. This index was originally developed for pulmonary vein isolation as well as other left atrial procedures. The aim of our study is to evaluate the feasibility and efficacy of the AI for the ablation of the cavotricuspid isthmus (CTI) in patients presenting with typical atrial flutter (AFL). Methods and results: This prospective multicentre non-randomized study enrolled 412 consecutive patients with typical AFL undergoing AI-guided cavotricuspid isthmus ablation. The procedure was performed targeting an AI of 500 and an inter-lesion distance measurement of ≤6 mm. The primary endpoints were CTI 'first-pass' block and persistent block after a 20-min waiting time. Secondary endpoints included procedural and radiofrequency duration and fluoroscopic time. A total of 412 consecutive patients were enrolled in 31 centres (mean age 64.9 ± 9.8; 72.1% males and 27.7% with structural heart disease). The CTI bidirectional 'first-pass' block was reached in 355 patients (88.3%), whereas CTI block at the end of the waiting time was achieved in 405 patients (98.3%). Mean procedural, radiofrequency, and fluoroscopic time were 56.5 ± 28.1, 7.8 ± 4.8, and 1.9 ± 4.8 min, respectively. There were no major procedural complications. There was no significant inter-operator variability in the ability to achieve any of the primary endpoints. Conclusion: AI-guided ablation with an inter-lesion distance ≤6 mm represents an effective, safe, and highly reproducible strategy to achieve bidirectional block in the treatment of typical AFL. Graphical Abstract: